A Bibliometric Exploration of the Qualitative Research Literature in Distance Education Using A Network Approach. Issue 4 (1st October 2020) - Wolf, Sara E.; Andrzejewski, Carey E.; Clark, Dwayne A.; Forney, Kristine N.
ABSTRACT: Following repeated calls to ground the research surrounding distance education in theory, we engaged in a bibliometric exploration of the extant literature in order to determine the degree to which the field has been responsive to these calls. We focused on describing the trends – theoretical as well as methodological – of recent (2014–2018) qualitative scholarship in distance education, and we used network methods to explore connections within published work, established theories, and qualitative methodologies. We found that distance education researchers using qualitative research methods were likely to characterize their work as case study. We also found that although the field has been responsive to the critique that the work has been atheoretical, that response has produced a broad rather than focused foundation for research in distance education. That is, many individual studies are theoretically grounded, but the field has not identified a cohesive theoretical foundation. Appendices available: https://aub.ie/AJDE_DETheoryApp